Power distribution in three-layer planar dielectric guide with small circular deformation - Shukla P.K.; Choudhury P.K.; Khastgir P.; Ojha S.P. (My University, 2025)
A numerical estimation has been made of the distribution of power through the guiding region of a three-layer planar dielectric guide with a small circular deformation across the direction of propagation. Using the scalar field approximation the general expressions for the power in the guiding and non-guiding regions are derived. The fractional power in the guiding region is plotted against the dimensionless core parameter. The cases of three lowest azimuthal modal indices have been described.